2021
DOI: 10.1111/rec.13545
|View full text |Cite
|
Sign up to set email alerts
|

The resistance and short‐term resilience of a restored extracted peatland ecosystems post‐fire: an opportunistic study after a wildfire

Abstract: Bogs are known to be relatively resistant and resilient to fire, due to the dominance of wet Sphagnum mosses. Indeed, Sphagnum mosses by holding water, ensure bog resistance, and by regenerating from any fragments left post‐fire, ensure bog resilience. The return of several ecological attributes has been reported in the literature post‐restoration. However, the resistance and resilience have not yet been evaluated in restored peatlands. A fire affecting an extracted peatland restored 10 years ago provided the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…However, we found that following wildfires on sites of conservation interest with relatively high plant diversity, the species composition shifts toward common, pioneer species and away from characteristic upland species. Wildfires similarly may affect communities in “wet hollows” more than those forming a dense “lawn” due to the latter's better water retention (Blier‐Langdeau et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that following wildfires on sites of conservation interest with relatively high plant diversity, the species composition shifts toward common, pioneer species and away from characteristic upland species. Wildfires similarly may affect communities in “wet hollows” more than those forming a dense “lawn” due to the latter's better water retention (Blier‐Langdeau et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In August 2014, an accidental fire burned nine hectares of the restored site; seven hectares remained intact, allowing for comparison between burnt and intact areas. Lawn-adapted species Sphagnum Acutifolia and Eriophorum sedges lost less biomass than their wetter hollow counterparts, which were dominated by Sphagnum Cuspidata and Scirpus sedges 73 . With that said, all sites-including the hollows-rapidly recovered.…”
Section: Peatland Resiliencementioning
confidence: 92%
“…We also present evidence that biodiversity, hydrological regime, and peat structure may not be fully restored or maintained, or may take decades to return (if at all), which is why the resilience of restored peatlands is put into question 72 . Still, it has been argued that restoration actions provide some resilience when compared to degraded sites 73 .…”
Section: Peatland Resiliencementioning
confidence: 99%
“…Considering ongoing increases in atmospheric carbon and rising global temperatures, a rapid return of typical peatland vegetation is crucial to minimise the loss of previously locked‐up carbon (Nugent et al, 2019). The restoration of peatland vegetation and subsequent ecohydrological processes can also enhance the resistance and resilience of restored peatlands and minimise carbon loss to future extreme climatic events (Blier‐Langdeau et al, 2022; Loisel & Gallego‐Sala, 2022). Consequently, additional restoration action may be necessary along with rewetting to push restored peatlands towards pre‐disturbed states and ensure the long‐term stability of restored peatlands (Granath et al, 2016).…”
Section: Introductionmentioning
confidence: 99%